The new exploration of pure total flavonoids extracted from Citrus maxima (Burm.) Merr. as a new therapeutic agent to bring health benefits for people - Ding, Shuning; Wang, Peipei; Pang, Xi; Zhang, Leyin; Qian, Lihui; Jia, Xinru; Chen, Wenqian; Ruan, Shanming; Sun, Leitao (Frontiers in Nutrition, 2022)
The peel and fruit of Citrus varieties have been a raw material for some traditional Chinese medicine (TCM). Pure total flavonoids from Citrus maxima (Burm) Merr. (PTFC), including naringin, hesperidin, narirutin, and neohesperidin, have been attracted increasing attention for their multiple clinical efficacies. Based on existing in vitro and in vivo research, this study systematically reviewed the biological functions of PTFC and its components in preventing or treating liver metabolic diseases, cardiovascular diseases, intestinal barrier dysfunction, as well as malignancies. PTFC and its components are capable of regulating glycolipid metabolism, blocking peroxidation and persistent inflammation, inhibiting tumor progression, protecting the integrity of intestinal barrier and positively regulating intestinal microbiota, while the differences in fruit cultivation system, picking standard, manufacturing methods, delivery system and individual intestinal microecology will have impact on the specific therapeutic effect. Thus, PTFC is a promising drug for the treatment of some chronic diseases, as well as continuous elaborate investigations are necessary to improve its effectiveness and bioavailability.